1988
DOI: 10.1037/0022-0167.35.3.311
|View full text |Cite
|
Sign up to set email alerts
|

Stereotypic views of medical educators toward students with a history of psychological counseling.

Abstract: Research has demonstrated that attitudes toward persons who seek psychological counseling are complex. Both favorable and unfavorable characteristics have been attributed to such individuals. However, generalizability of findings to real world circumstances is limited because conclusions have typically been based on studies using college undergraduates in the role of decision makers. The purpose of our study was to determine the extent to which a history of psychological counseling influenced actual decision m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 13 publications
3
18
0
Order By: Relevance
“…After combining different grammatical forms of the same word (Fehr, 1988), 160 characteristics remained, including characteristics that align with those previously documented by past research on perceptions of mental illness and professional psychological help seeking (e.g., dependent, emotional, helpless, indecisive, lonely, weak; P. T. King, Newton, Osterlund, & Baber, 1973;Oppenheimer & Miller, 1988;Ryan, Robinson, & Hausmann, 2001;Sibicky & Dovidio, 1986). Participants generated a mean of 7.23 (SD = 2.43) characteristics.…”
Section: Methodssupporting
confidence: 68%
“…After combining different grammatical forms of the same word (Fehr, 1988), 160 characteristics remained, including characteristics that align with those previously documented by past research on perceptions of mental illness and professional psychological help seeking (e.g., dependent, emotional, helpless, indecisive, lonely, weak; P. T. King, Newton, Osterlund, & Baber, 1973;Oppenheimer & Miller, 1988;Ryan, Robinson, & Hausmann, 2001;Sibicky & Dovidio, 1986). Participants generated a mean of 7.23 (SD = 2.43) characteristics.…”
Section: Methodssupporting
confidence: 68%
“…This may be because the public in general tends to provide negative descriptions of individuals who experience mental illness (Crisp, Gelder, Rix, Meltzer, & Rowlands, 2000). A history of having sought outpatient mental health services can lead others to have more negative perceptions of the individual (Dovidio, Fishbane, & Sibicky, 1985), including being labeled more awkward, cold, defensive, dependent, insecure, sad, and unsociable (Sibicky & Dovidio, 1986); to view that individual as less in control of her or his emotions (Oppenheimer & Miller, 1988); and to describe the individual as weak or disturbed (King, Newton, Osterlund, & Baber, 1973). Some researchers have also found that being labeled a "former mental hospital patient" led to greater social rejection than was true for someone with no such label (Link, Cullen, Frank, & Wozniak, 1987).…”
Section: Social Stigmamentioning
confidence: 99%
“…Oppenheimer and Miller (1988) reported that a sample of 523 training directors of graduate medical training programs tended to perceive students who received psychological counseling as less competent, less reliable, less of a leader, more dependent, more indecisive, and more emotional when compared with students who had not sought help. Sibicky and Dovidio (1986) recruited 136 undergraduates for an experiment in which participants were asked to rate a conversational partner (whom they were told had been recruited either from among students seeking psychological therapy or from students in an introductory psychology course, the independent variable) on 38 bipolar scales (e.g., shy-bold, friendlyunfriendly).…”
Section: Help-seeker Stereotypesmentioning
confidence: 99%